Effect on Time Domain Parameters of HRV after Slow Breathing Exercise in Type 2 Diabetes Mellitus - Yesmin, Jenefer; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2017)
Background: Cardiac autonomic nerve dysfunction has been associated with Type 2 Diabetes Mellitus (T2DM) with reduced Heart Rate Variability (HRV). Regular practice of slow breathing exercise (SBE) improves cardiac autonomic nerve function. Objective: To assess the effects of slow breathing exercise on cardiac autonomic nerve function by analysis of HRV in patients with Type 2 Diabetes Mellitus (T2DM). Methods: This prospective interventional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University in 2015. For this, total 30 male diagnosed T2DM patients from the Out Patient Department of Endocrinology, BSMMU aged 45-55 years with diseases duration of 5-10 years were included in the study group. All the patients underwent slow breathing exercise (SBE -30 mins twice daily) for 3 months along with medical treatment. Mean heart rate (HR), mean R-R interval, standard deviation of the NN intervals (SDNN), Square root of mean squared differences of successive N-N intervals (RMSSD) of HRV parameters were recorded at the beginning of 3 months and also at the end of 3 months of study period. Thirty age, BMI matched healthy subject also included as control. For statistical analysis paired and unpaired sample t-test were done as applicable. Results: In this study, Pre-exercise value of mean HR was significantly higher (p< 0.001) and Pre-exercise values of mean R-R interval, SDNN and RMSSD were significantly lower (p< 0.001) in diabetic patients in comparison to control. After 3 months of performing SBE, post exercise values of all parameters were improved significantly (p< 0.001). Conclusion: The results of this study revealed that SBE has some beneficial effects on cardiac autonomic balance in T2DM patients. Bangladesh Soc Physiol. 2017, June; 12(1): 15-20